A method for preparing a silicon-based composite photoelectrode
Through selective corrosion, the combination of silicon nanofibers and composite materials has been solved, and the problem of high cost of silicon-based photoelectrode preparation is achieved, low-cost and efficient silicon-based composite photoelectrode preparation is improved, and the conductivity and photoelectric reaction performance are improved. Suitable for industrial production.
Patent Information
- Application Number
- CN202211340824.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicon-based photoelectrode preparation process is costly and difficult to mass produce, which limits the industrial application of silicon-based photoelectrodes.
The combination of silicon nanofibers and composite materials was prepared by selective corrosion, and the aluminum matrix material was removed by electrochemical methods, and acetylene black and adhesive PVDF were mixed to form a silicon-based composite photoelectrode, simplifying the process flow and reducing costs.
It realizes low-cost and efficient preparation of silicon-based composite photoelectrodes, improves the conductivity and photoelectric reaction performance of silicon nanofibers, is suitable for large-area industrial production, and maintains stable photosensitiveness after multiple uses.
Smart Images

Figure CN115616054B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectrode preparation, and specifically relates to a method for preparing a silicon-based composite photoelectrode. Background Art
[0002] As a good photoelectrode material, silicon has received extensive attention from researchers in recent years. Silicon is not only abundant on the earth and relatively cheap, but also has a band gap of about 1.12eV. The spectral response range is very wide, and there are few internal defects in crystalline silicon, with high carrier mobility and carrier lifetime. In existing studies, researchers mostly use the method of depositing or doping precious metals to modify the silicon surface, thereby improving the response effect of silicon-based electrodes. However, the expensive preparation process price and the difficult technology for mass production are still difficult to break through for the entire silicon-based photoelectrode field.
[0003] Therefore, there is an urgent need in the art for an efficient, stable and low-cost method for preparing silicon-based composite photoelectrodes. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a silicon-based composite photoelectrode, which is simple to operate and has a low preparation cost, and the prepared silicon-based photoelectrode has a good photoelectric reaction.
[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a silicon-based composite photoelectrode, which combines silicon nanofibers prepared by selective etching with a composite material to assemble a silicon-based composite photoelectrode, comprising the following steps:
[0006] Step 1: Cut the aluminum-silicon eutectic alloy into rod-shaped specimens and grind their surfaces smooth;
[0007] Step 2: placing the rod-shaped sample into a ceramic tube, and performing directional growth in a directional solidification furnace at a set heating temperature and growth rate, thereby preparing the desired eutectic silicon alloy structure;
[0008] Step 3: The aluminum matrix material is removed by electrochemical etching, and the silicon nanofiber structure falls off from the matrix and enters the corrosion solution;
[0009] Step 4: Filter and dry the corroded solution to obtain silicon nanofiber structure powder; mix the obtained silicon nanofiber structure powder with acetylene black and adhesive PVDF, adjust it into a sol state with NMP as solvent, and then apply it on ITO conductive glass to obtain a positive electrode sheet.
[0010] Furthermore, in step 1, the aluminum-silicon eutectic alloy adopts the industrial ZL102 aluminum-silicon eutectic alloy.
[0011] Furthermore, in step 2, the heating temperature is 800° C. and the insulation time is 30 minutes.
[0012] Furthermore, in step 2, the growth rate is 2 mm / s.
[0013] Furthermore, in step 3, the electrochemical corrosion method is specifically two-electrode electrolytic corrosion, a platinum electrode is used as an auxiliary electrode, a working electrode is a directionally grown aluminum-silicon eutectic alloy, the corrosion potential is 0.5V, the corrosion solution is 0.1M HCL solution, and the corrosion time is 12h.
[0014] Furthermore, in step 4, the corroded liquid is cleaned and filtered with deionized water, hydrofluoric acid and ethanol in sequence.
[0015] Furthermore, in step 4, the mixing mass ratio of the silicon nanofiber structure powder to acetylene black and PVDF is 8:1:1 or 8:2:1.
[0016] Furthermore, after the positive electrode sheet was obtained, the electrochemical performance of the obtained positive electrode sheet was tested using a three-electrode electrolytic cell system under ultraviolet light with a wavelength of 405 nm.
[0017] Furthermore, the electrolyte of the three-electrode electrolysis system is 0.2 mol / L KNO3, a saturated calomel electrode is used as a reference electrode, a platinum electrode is used as an auxiliary electrode, the working electrode is the prepared positive electrode sheet, and the electrode applied potential is 0.1V.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1) Compared with other photoelectrode preparation methods that require deposition modification or precious metal doping, this method has simple process, convenient operation, high success rate, and is conducive to large-scale industrial production.
[0020] 2) As a semiconductor element, silicon is relatively weak in multi-directional conductivity. The present invention uses acetylene black with good conductivity as a mixing agent to enhance the conductivity of silicon-based materials and greatly improve the defect of poor conductivity of silicon nanofibers.
[0021] 3) The silicon-based composite photoelectrode prepared by the present invention has a good cycle life, can maintain relatively stable photosensitivity after repeated irradiation by an external light source, and has a good photoelectric reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A flowchart of a method implementation of an embodiment of the present invention;
[0023] Figure 2 This is a morphological diagram of the silicon nanofiber structure extracted in an embodiment of the present invention;
[0024] Figure 3 The EDS energy spectrum analysis result of the silicon nanofibers extracted in the embodiment of the present invention;
[0025] Figure 4 This is a current density diagram of a three-electrode test when silicon nanosheets: acetylene black: PVDF = 8:1:1 in an embodiment of the present invention;
[0026] Figure 5 This is a current density diagram of a three-electrode test when silicon nanofiber: acetylene black: PVDF = 8:1:1 in an embodiment of the present invention;
[0027] Figure 6 This is a current density diagram of a three-electrode test when the ratio of silicon nanofiber: acetylene black: PVDF = 8:2:1 in an embodiment of the present invention. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0029] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0031] like Figure 1 As shown, this embodiment provides a method for preparing a silicon-based composite photoelectrode, by combining silicon nanofibers prepared by selective etching with a composite material to assemble a silicon-based composite photoelectrode; specifically, the following steps are included:
[0032] Step 1: Use the common ZL102 aluminum-silicon eutectic alloy on the market, cut it into rod-shaped specimens, and polish its surface smoothly.
[0033] In this embodiment, it is wire-cut into cylindrical test bars with a diameter of 7 mm and a length of 90 mm.
[0034] Step 2: Place the rod-shaped sample into a ceramic tube, and perform directional growth in a directional solidification furnace at a set heating temperature and growth rate to prepare the desired eutectic silicon alloy structure.
[0035] In this embodiment, the heating temperature is 800° C., the holding time is 30 min, and the growth rate is 2 mm / s.
[0036] Step 3: The aluminum matrix material is removed by electrochemical corrosion, and the silicon nanofiber structure falls off from the matrix and enters the corrosion solution.
[0037] In this embodiment, the alloy rod after directional growth is cut into thin slices, the surface is polished to a mirror surface after mounting, and the aluminum matrix material is selectively corroded and removed in a constant potential of 0.5V and 0.1M HCl. The silicon nanofiber structure falls off from the matrix and enters the solution. The silicon nanofiber structure in the solution can be extracted by filtration.
[0038] In this embodiment, the electrochemical corrosion method is specifically two-electrode electrolytic corrosion, a platinum electrode is used as an auxiliary electrode, a working electrode is a directionally grown aluminum-silicon eutectic alloy, the corrosion potential is 0.5V, the corrosion solution is 0.1M HCL solution, and the corrosion time is 12h.
[0039] Step 4: The corroded solution is washed with deionized water, hydrofluoric acid, and ethanol in turn, filtered and dried to obtain silicon nanofiber structure powder; the obtained silicon nanofiber structure powder is mixed with acetylene black and adhesive PVDF, and adjusted into a sol state with NMP as solvent; then a small amount of liquid is sucked with a pipette onto the surface of the ITO conductive glass, and evenly coated with a glass rod, and the positive electrode is obtained after sufficient drying.
[0040] In this embodiment, the mixing mass ratio of the silicon nanofiber structure powder to acetylene black and PVDF is 8:1:1 or 8:2:1.
[0041] Step 5: Under ultraviolet light with a wavelength of 405 nm, the electrochemical performance of the obtained positive electrode sheet is tested using a three-electrode electrolytic cell system, and the change in current density is recorded.
[0042] In this embodiment, the electrolyte of the three-electrode electrolysis system is 0.2 mol / L KNO3 solution, a saturated calomel electrode is used as a reference electrode, a platinum electrode is used as an auxiliary electrode, the working electrode is the prepared positive electrode sheet, and the electrode applied potential is 0.1V.
[0043] Example 1
[0044] a) Cut the ZL102 aluminum-silicon eutectic alloy into cylindrical rods with a diameter of 7 mm and a length of 90 mm, and cut the test rods into thin slices with a thickness of 1.5 mm. After mounting, the surfaces were polished smooth with 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh and 2000 mesh water-abrasive sandpaper, and the surfaces were polished to a mirror surface with diamond paste. The polished samples were subjected to electrochemical selective corrosion, using constant potential electrolysis, two-electrode electrolytic corrosion, the corrosion equipment was an electrochemical workstation, the corrosion potential was 0.5 V, the corrosion solution was 0.1 M HCl, and the corrosion time was 12 h.
[0045] b) After filtering the etching solution containing silicon nanosheet structure with deionized water, stir and place it in a 2% HF solution for 2 hours to dissolve the SiO2 on the surface. Then wash and filter it twice with deionized water, and finally wash and filter it twice with ethanol and dry it. Mix silicon nanosheets, acetylene black, and binder PVDF in a mass ratio of 8: 1: 1, and stir them in a magnetic stirrer for 1 hour to mix them evenly. Then use NMP as the solvent, add an appropriate amount of NMP solvent to make it sol-like, then use a pipette to quantitatively absorb and drop it on the surface of ITO conductive glass, and use a glass rod to roll and coat it to make it evenly distributed.
[0046] c) Cut a copper wire of appropriate length and diameter of 0.3mm to contact the ITO conductive glass coating surface, and cover the contact part with an appropriate amount of conductive silver paste to ensure the conductivity of the wire and the electrode sheet. Finally, put it in a vacuum drying oven and dry it at 80℃ for 12 hours to obtain the positive electrode sheet.
[0047] d) The electrochemical performance of the synthesized sample was tested using a three-electrode experimental cell system. The saturated calomel electrode was used as the reference electrode, the platinum electrode was used as the auxiliary electrode, the working electrode was the prepared silicon-based positive electrode, the applied potential was 0.1V, and the electrolyte was 0.2mol / L KNO3. After the electrolytic cell was powered on, a UV laser with a wavelength of 405nm was used to irradiate the surface of the silicon-based composite electrode, and the current density change was recorded at the same time. The results are shown in Figure 2. Figure 4 shown.
[0048] Example 2
[0049] a) Cut ZL102 aluminum-silicon eutectic alloy into cylindrical rods with a diameter of 7 mm and a length of 90 mm, polish them with sandpaper and put them into a corundum tube with a diameter of 7 mm. Use a directional solidification furnace for directional growth. The heating temperature is 800℃, the holding time is 30 min, the coolant is water, and the growth rate of the test rod is 2 mm / s.
[0050] b) Cut the directional growth test rod into a thin slice with a thickness of 1.5 mm. After mounting, the surface was polished with 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh and 2000 mesh water-abrasive sandpaper, and the surface was polished to a mirror surface with diamond paste. The polished sample was subjected to electrochemical selective corrosion, using constant potential electrolysis, two-electrode electrolytic corrosion, the corrosion equipment was an electrochemical workstation, the corrosion potential was 0.5 V, the corrosion solution was 0.1M HCL, and the corrosion time was 12 hours.
[0051] c) After filtering the etching solution containing silicon nanosheet structure with deionized water, stir and place it in a 2% HF solution for 2 hours to dissolve the SiO2 on the surface. Then wash and filter it twice with deionized water, and finally wash and filter it twice with ethanol and dry it. Figure 2 This is the extracted silicon nanowire fiber structure diagram. Figure 3 For the corresponding EDS analysis. Silicon nanofibers, acetylene black, and binder PVDF were mixed in a mass ratio of 8: 1: 1 and stirred in a magnetic stirrer for 1 hour to make them evenly mixed. Then, NMP was used as a solvent, and an appropriate amount of solvent was added to make a sol state, and then quantitatively sucked and dropped onto the surface of the ITO conductive glass with a pipette, and a glass rod was used to roll and coat it to make it evenly distributed.
[0052] d) Cut a copper wire of appropriate length and diameter of 0.3 mm to contact the ITO conductive glass coating surface, and cover the contact part with an appropriate amount of conductive silver paste to ensure the conductivity of the wire and the electrode sheet. Finally, put it in a vacuum drying oven and dry it at 80°C for 12 hours to obtain the positive electrode sheet.
[0053] e) The electrochemical performance of the synthesized sample was tested using a three-electrode experimental cell system. The saturated calomel electrode was used as the reference electrode, the platinum electrode was used as the auxiliary electrode, the working electrode was the prepared silicon-based positive electrode sheet, the working potential was 0.1V, and the electrolyte was 0.2mol / L KNO3. After the electrolytic cell was powered on, a blue-violet laser with a wavelength of 405nm was used to irradiate the surface of the silicon-based composite electrode, and the current density change was recorded at the same time. The results are shown in Figure 2. Figure 5 shown.
[0054] Example 3
[0055] a) ZL102 aluminum-silicon eutectic alloy was cut into cylindrical rods with a diameter of 7 mm and a length of 90 mm. After being polished with sandpaper, they were loaded into a corundum tube with a diameter of 7 mm. Directional growth was carried out in a directional solidification furnace with a heating temperature of 800 °C and a holding time of 30 min. The coolant was water and the growth rate of the test rod was 1 mm / s.
[0056] b) Cut the directional growth test rod into a thin slice with a thickness of 1.5 mm. After mounting, the surface was polished with 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, 1500 mesh and 2000 mesh water-abrasive sandpaper, and the surface was polished to a mirror surface with diamond paste. The polished sample was subjected to electrochemical selective corrosion, using constant potential electrolysis, two-electrode electrolytic corrosion, the corrosion equipment was an electrochemical workstation, the corrosion potential was 0.5 V, the corrosion solution was 0.1M HCL, and the corrosion time was 12 hours.
[0057] c) After filtering the etching solution containing silicon nanosheet structure with deionized water, stir and place it in a 2% HF solution for 2 hours to dissolve the SiO2 on the surface. Then wash and filter it twice with deionized water, and finally wash and filter it twice with ethanol and dry it. Mix silicon nanofibers, acetylene black, and binder PVDF in a mass ratio of 8: 2: 1, stir in a magnetic stirrer for 1 hour to mix them evenly. Then use NMP as the solvent, add an appropriate amount of solvent to make a sol, then use a pipette to quantitatively absorb and drop it on the surface of the ITO conductive glass, and use a glass rod to roll and coat it to make it evenly distributed.
[0058] d) Cut a copper wire of appropriate length and diameter of 0.3 mm to contact the ITO conductive glass coating surface, and cover the contact part with an appropriate amount of conductive silver paste to ensure the conductivity of the wire and the electrode sheet. Finally, put it in a vacuum drying oven and dry it at 80°C for 12 hours to obtain the positive electrode sheet.
[0059] e) The electrochemical performance of the synthesized sample was tested using a three-electrode experimental cell system. The saturated calomel electrode was used as the reference electrode, the platinum electrode was used as the auxiliary electrode, the working electrode was the prepared silicon-based positive electrode sheet, the working potential was 0.1V, and the electrolyte was 0.2mol / L KNO3. After the electrolytic cell was powered on, a blue-violet laser with a wavelength of 405nm was used to irradiate the surface of the silicon-based composite electrode, and the current density change was recorded at the same time. The results are shown in Figure 2. Figure 6 shown.
[0060] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a silicon-based composite photoelectrode, characterized in that: The method combines silicon nanofibers prepared by selective etching with composite materials to assemble a silicon-based composite photoelectrode, including the following steps: Step 1: Cut the aluminum-silicon eutectic alloy into rod-shaped specimens and grind their surfaces smooth; Step 2: placing the rod-shaped sample into a ceramic tube, and performing directional growth in a directional solidification furnace at a set heating temperature and growth rate, thereby preparing the desired eutectic silicon alloy structure; Step 3: The aluminum matrix material is removed by electrochemical etching, and the silicon nanofiber structure falls off from the matrix and enters the corrosion solution; Step 4: filtering and drying the corroded solution to obtain silicon nanofiber structure powder; mixing the obtained silicon nanofiber structure powder with acetylene black and adhesive PVDF, adjusting it into a sol state with NMP as solvent, and then coating it on ITO conductive glass to obtain a positive electrode sheet; In the step 1, the aluminum-silicon eutectic alloy adopts the industrial ZL102 aluminum-silicon eutectic alloy; In step 2, the heating temperature is 800°C, the holding time is 30 minutes, and the growth rate is 2 mm / s; In step 3, the electrochemical corrosion method is specifically two-electrode electrolytic corrosion, a platinum electrode is used as an auxiliary electrode, a working electrode is a directionally grown aluminum-silicon eutectic alloy, the corrosion potential is 0.5V, the corrosion solution is a 0.1M HCL solution, and the corrosion time is 12h; In the step 4, the corroded liquid is washed and filtered with deionized water, hydrofluoric acid, and ethanol in sequence; the mixing mass ratio of the silicon nanofiber structure powder to acetylene black and PVDF is 8:1:1 or 8:2:1; After obtaining the positive electrode sheet, the electrochemical performance of the obtained positive electrode sheet was tested using a three-electrode electrolysis system under ultraviolet light with a wavelength of 405nm; the electrolyte of the three-electrode electrolysis system was 0.2mol / L KNO3, a saturated calomel electrode was used as a reference electrode, a platinum electrode was used as an auxiliary electrode, the working electrode was the prepared positive electrode sheet, and the electrode applied potential was 0.1V.
Citation Information
Patent Citations
Preparation method of single crystal copper nanowire
CN114855274A
Negative electrode for lithium-based batteries
US20160172665A1